(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
Textiles applications in technical area is one of the imperative subjects in present time. Application of textiles in various fields especially in protective garments application is increasing day by day. The objective of this work is to evaluate and discover the effect of fiber and structure on tensile and dynamic mechanical properties of hybrid and non-hybrid basalt structures. This work deals with the study of the mechanical properties of woven fabrics in relation to fiber and weave. In this study, investigative experiments are carried out to find out the static and dynamic mechanical behaviour of Basalt ⁄ Polyester (B ⁄ PET) and Basalt ⁄ Polypropylen (B ⁄ PP) fibre hybrid woven and non-hybrid woven fabric. Three types of weaves are used i.e. Plain (PW), Matt (MW) and 1 ⁄ 3 Twill (TW) for hybrid and non-hybrid structures respectively. The tensile testing of all the woven fabric specimens is carried out. The discussion of results is in terms of fibre effect and woven geometry. The exposure of fabrics to increasing temperature is beneficial to their mechanical properties and performance. The dynamic mechanical analysis exhibits a rise in storage modulus. It indicates a lower damping and higher stiffness ratio in hybrid fabrics. These fabrics can be used for temperature resistant applications and in composites.